(untitled) (Research, Society and Development, 2019)
There are several accidents that occur due to the lack of a detailed inspection, due to a detailed technical report. In this sense, the objective research is to carry out a technical expertise in the area of engineering in a municipality of Nova Módica / MG by means of a case study.Thus, in the course of the research will be drawn reflections on the importance of reports and judicial expertise in the area of engineering, considerations regarding its elaboration and also some of the possible pathologies found in the buildings, which cause damage to the structures. Professionals qualified to prepare a technical report need to be constantly trained and trained to evaluate the location, type of damage or anomaly involved in the structure, given that it is a document of great importance to the engineering area. However, the absence of inspections, detailed inspection tends to cause various accidents and pathologies to buildings. To discuss the theme in focus, the study is based on well known authors and articles, with the purpose of helping to understand the problem outlined and the objectives proposed by means of a bibliographic study of a described and qualitative character, with the purpose of studying the information and their concepts and / or definitions as well as their applications, highlighting the importance of the expert in civil engineering to deal with cases that involve processes associated with the pathologies in the constructions.